(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
Motivation is a key factor in successful foreign language learning. Teachers play a critical role in fostering and maintaining students’ motivation through effective strategies, classroom practices, and supportive learning environments. This article explores the role of teachers in enhancing motivation, discusses specific strategies for engaging learners, and highlights the impact of teacher behavior on student outcomes in foreign language education.